Prevalence and Anatomical Variations of Middle Hepatic Artery: A Cadaveric and Radiological Study - Khatiwada, Sagar; Belbase, Narayan Prasad; Yadav, Prasun; Ojha, Khagendra; Upadhyay, Hari Prasad (Journal of College of Medical Sciences-Nepal, 2024)
Introduction Middle Hepatic Artery is a hilar artery that supplies segment IV of the left hemi-liver. Anatomical Variations of this hilar artery has led to its classification into various sub-types based on its origin. Many studies have elucidated the surgical importance of MHA and in-depth knowledge of its variations is essential to minimize the morbidity during liver surgeries. In LDLT and during hepatic resections any injury to MHA and vascular compromise to Segment IV can bring in catastrophic consequences such as reduction in functional volume of left lobe in right allograft, possible graft loss in left allograft and ischemic cholangiopathy at all cases. Methods This is a cross-sectional study on 25 cadaveric Livers and 25 CECT- Abdomen arterial phase, a total of 50 Liver specimens at our center. The origin and course of MHA was accessed and characterized after meticulous dissection of cadavers and 3D reconstruction of CECT-Abdomen arterial phase. Collected data was entered and analyzed by using IBM SPSS STATISTICS 16. Results MHA was present in 76% of cases. MHA originated from RHA in 34% of cases; from LHA in 24% of cases; from RHA in presence of replaced LHA in 6%; from LHA in presence of replaced RHA in 8% and from non-left non-right hepatic artery along the axis of CHA in 4% of cases. Conclusion MHA is a hilar artery that predominately originates from RHA. It is very important for a surgeon to meticulously study the course of MHA in patients prior to liver surgeries using 3D-reconstruction of radiological images to minimize morbidities.